Azastilbene Analogs as Tyrosinase Inhibitors: New Molecules with Depigmenting Potential - Larissa Lavorato Lima; Rebeca Mól Lima; Annelisa Farah da Silva; Antônio Márcio Resende do Carmo; Adilson David da Silva; Nádia Rezende Barbosa Raposo (The Scientific World Journal)
This research has been an effort to develop synthetic resveratrol analogs in order to improve the depigmenting potential of natural resveratrol. Six resveratrol analogs were synthesized and tested for tyrosinase inhibitory activity in vitro, by qualitative and quantitative steps. The results showed the analog C as being the most powerful tyrosinase inhibitor (IA50 = 65.67 ± 0.60 μg/mL), followed by the analogs B, E, F, A, and D, respectively. The analog C presented a tyrosinase inhibition potential better than natural resveratrol (P<0.001). The best depigmenting activity was provided by the presence of hydroxyl in the orthoposition on the second phenolic ring.